Characteristics of Nasal Foreign Body Cases in Dr. Hasan Sadikin General Hospital Bandung - Henzen Ghesan Hampry; Sinta Sari Ratunanda; Melati Sudiro; Wijana Wijana; Ayu Hardianti Saputri (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Nasal foreign bodies are caused by the insertion of an extraneous substance into the nasal cavity. These cases frequently occur in children. Nasal foreign bodies are easily diagnosed, yet the treatment may be burdensome with possible complications and costly management. The study aimed to evaluate the characteristics of nasal foreign body cases.Methods: The study was descriptive and cross-sectional, using secondary data taken from all medical records of the Emergency Room in Dr. Hasan Sadikin General Hospital, Bandung, from 2018 to 2021. Data were presented in tables.Results: Of the 57 cases, most of the patients (64.9%) were aged 3-5 years, with boys as the most prevalent cases (59.7%) and the most common complaint was pain (31.7%). Inorganic foreign bodies (61.4%) were more commonly found, and being frequently found in the right nasal cavity (49.1%). The duration of the foreign body in the nasal cavity and the treatment conducted on the patients were mostly not written in the medical records, however, no complications were found.Conclusions: A higher incidence of nasal foreign bodies can be found in boys aged 3-5 years. Inorganic objects and pain are the most common manifestations, although the condition of all patients has been improved. Raising awareness about foreign body cases to the community, especially the parents, is the key to preventing these cases from occurring.